2021
DOI: 10.14744/nci.2021.55938
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Frail Older Adults: Associations and Gender Difference

Abstract: Objective: Depression is highly prevalent in frail older adults and both clinical situations share similar clinical and prognostic factors. The aim of this study was to investigate the relationship between frailty and depression by considering each component of frailty, in both genders. Methods: Six hundred and forty-one patients aged 60 years and older, admitted to a Geriatrics outpatient clinic in a tertiary hospital, were included in this cross-sectional study. FRIED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
1
5
0
1
Order By: Relevance
“…The strongest association was observed with FS, especially with HGS in the men, whereas in the women there was no such a strong relationship. Depression also turned out to be, to a certain extent, a determinant of FS in both sexes, which is also confirmed by many available scientific reports [34,[37][38][39][40][41]. Our research has shown that widowhood is one of the risk factors for FS.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The strongest association was observed with FS, especially with HGS in the men, whereas in the women there was no such a strong relationship. Depression also turned out to be, to a certain extent, a determinant of FS in both sexes, which is also confirmed by many available scientific reports [34,[37][38][39][40][41]. Our research has shown that widowhood is one of the risk factors for FS.…”
Section: Discussionsupporting
confidence: 86%
“…In a cross-sectional study conducted by Thinuan et al the existence of such a relationship was confirmed, especially in developed countries [34]. Research conducted by Firuzan et al confirms that depression may have an important role in the development of FS in both sexes [37]. Furthermore, in the study of Boyer et al a large part of cohort was frail or pre-frail and presented signs of loss of independence, which may be explained by multiple factors including poor FA and depression [38].…”
Section: Discussionmentioning
confidence: 87%
“…Neste estudo, pode-se aventar a possibilidade de que depressão tenha sido a variável ordenadora dos riscos uma vez que sua presença isolada, e posteriormente, combinada com fragilidade, representou riscos superiores ao da condição de fragilidade isoladamente 35 . Na agenda de investimentos futuros de pesquisa sobre a temática, as análises de mortalidade por todas as causas deverão comparar os efeitos representados pelas associações de depressão com os níveis de fragilidade, com cada um dos seus critérios e com a pré-fragilidade, com ajustes por doenças específicas, como por exemplo as cardiovasculares 30 .…”
Section: Discussionunclassified
“…In this study, it seems reasonable to affirm that depression was the ordering variable of the risks, since its presence in isolation, and again in combination with frailty, represented higher risks than the condition of frailty alone 35 . In future research on the subject, analyzes of all-cause mortality should aim to compare the effects represented by the associations of depression with the levels of frailty, with each of its criteria and with pre-frailty, with adjustments for specific diseases, for example, cardiovascular diseases 30 .…”
Section: Discussionmentioning
confidence: 53%